2021
DOI: 10.1088/1748-605x/ac3680
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing fibrin hydrogel toward effective neural progenitor cell delivery in spinal cord injury

Abstract: Transplantation of neural progenitor cell (NPC) possessing the potential to differentiate into neurons may guard against spinal cord injury (SCI)- associated neuronal trauma. We propose that autologous-like NPC may reduce post-transplant immune response. The study used the rat SCI model to prove this concept. For isolation and expansion of rat NPC for cell-based SCI therapy, the in vitro protocol standardized with human NPC seemed suitable. The primary aim of this study is to select a cell/neural tissue-compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Using lineage-committed cells and biomaterials can resolve this issue to a great extent. 70 The protocol we employed for culturing 39,64,68 has been shown to express the functional neuronal marker synaptophysin and the astrocyte marker GFAP was minimum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using lineage-committed cells and biomaterials can resolve this issue to a great extent. 70 The protocol we employed for culturing 39,64,68 has been shown to express the functional neuronal marker synaptophysin and the astrocyte marker GFAP was minimum.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of ADMSC properties like proliferation and transdifferentiation might get affected after in vivo transplantation, especially because of the injury site environment. Using lineage-committed cells and biomaterials can resolve this issue to a great extent . The protocol we employed for culturing ,, has been shown to express the functional neuronal marker synaptophysin and the astrocyte marker GFAP was minimum.…”
Section: Discussionmentioning
confidence: 99%
“…gradable hydrogels or glues with a high liquid content and the ability to hold cells after polymerization are formed, promoting adhesion, viability, proliferation and differentiation of cells [15][16][17][18]. It was shown that after implantation of a 3D-aligned fibrin hydrogel in rats with SC hemisection, the reconstruction of nerve fibers and blood vessels at the site of damage occurred (4 weeks), as well as the sprouting of a new axon completely through the damaged area (8 weeks) [8].…”
Section: Methodsmentioning
confidence: 99%
“…Fibrin is a common raw material for protein-based hydrogels. Sudhadevi et al (2021) synthesized a fibrin hydrogel loaded with neural progenitor cells (NPCs). Fibrin hydrogel is composed of a fibrinogen solution mixed with thrombin.…”
Section: Treatment Strategies Of Hydrogels As Scaffolds and Delivery ...mentioning
confidence: 99%